Offshore Financial Centers : The Assessment Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper updates Executive Directors on the progress since February 2005 in implementing the second phase of the offshore financial center (OFC) program as agreed in November 2003 (see PIN No. 03/138 at http://www.imf.org). At that time, Directors recognized that OFCs could pose prudential and financial integrity risks to the international financial system. In this context, Directors agreed that the monitoring of OFCs' activities and their compliance with supervisory and integrity standards should become a standard component of the financial sector work of the Fund. They also requested periodic updates on the progress with implementation of the program. Earlier updates were provided in March 2004 (Offshore Financial Centers-The Assessment Program-An Update) and February 2005 (Offshore Financial Centers-The Assessment Program-A Progress Report). With the completion of the first round of assessments, staff have begun implementing the second phase of the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Information Exchange; Information Framework Initiative; Information; Jurisdiction; PP; Aruba, Kingdom of the Netherlands